COVID-19 in the Time of Climate Change: Memetic Discourses on Social Media. Issue 7 (3rd October 2022) - Al-Rawi, Ahmed; Blackwell, Breanna; Kane, Oumar; O'Keefe, Derrick; Bizimana, Aimé-Jules
ABSTRACT : This paper analyzes the proliferation of memes linked to COVID-19 and climate change online discussions, looking particularly at how themes related to these two issues intersect with each other. To better understand the intersections, cross-pollinations, and mutations between these different but related forms of information dissemination, our research is based on applied thematic analysis and empirically analyzes memes deployed through two popular social media platforms (Facebook and Instagram). Both issues pose existential threats to humans, and studying the connection between the two through social media memetic discourses offers important empirical insight into ordinary users' views. The findings reveal eight themes that show different kinds of relations between COVID-19 and climate change. Memes present COVID-19 either as a solution or as a problem to climate change; they portray different effects between COVID-19 and climate change, and some consider both of them as hoaxes and/or conspiracies. Similarly, to previous studies, we see a relationship between political ideologies and views on climate change and COVID-19. Additionally, our findings show that believing climate change as a hoax and/or conspiracy is also linked to the same view that COVID-19 is fake. We also found a reasonably even spread of themes across both Instagram and Facebook, indicating that these social platforms do not harbor a clear ideological split.